(untitled) (diségno, 2026)
This essay focuses on one of the great wonders of the built world –the Pantheon, constructed around 126 AD– and, through drawing, proposes a possible clue as to how its form may have been generated in relation to human perspective. The oculus is interpreted as a lens, connecting the individual viewer to the infinity beyond. Between the circular opening above and the finite point of the observer below, an invisible geometry is formed: the cone. This central cone is understood as the building’s generative DNA, closely aligned with the internal workings of the human eye and the stereographic cones through which we perceive the world. [read more]